Guide d'écriture inclusive - Institut de recherches et d'études féministes (FéminÉtudes, 2020)
FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; féminétudes; genre; histoire et politique; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; périodes historiques; queer; québec; ressource en ligne; régions géographiques; thématiques; écriture inclusive

Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth; Lépinard, Éléonore (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques

L’intervention féministe sous l’influence de l’intersectionnalité : enjeux organisationnels et communicationnels au sein des organismes féministes au Québec - Marchand, Isabelle; Corbeil, Christine; Boulebsol, Carole (Communiquer. Revue de communication sociale et publique, 2020)
Au Québec, l’intervention féministe se déploie significativement au milieu des années 1970 et se présente comme une alternative, à la fois thérapeutique et politique, aux thérapies traditionnelles dans le champ de la santé mentale et de la lutte contre les violences sexistes, pour soutenir les femmes et défendre leurs droits. Elle repose, entre autres, sur la conscientisation et la reprise de pouvoir, à la fois individuelle et collective, dans une société marquée par la discrimination sexiste. Plus récemment, la popularité de l’intersectionnalité, comme cadre d’analyse théorique, politique et pratique, amène les intervenantes féministes francophones à adopter un regard critique sur leurs approches et leurs postures, en considérant notamment l’imbrication du sexisme avec d’autres formes d’oppression comme le racisme. À partir de plusieurs travaux menés au cours des dernières années auprès de praticiennes, les autrices proposent de réfléchir au développement récent de l’intervention féministe sous l’influence de l’intersectionnalité. Cet article suggère quelques pistes d’analyse sur les enjeux organisationnels et relationnels avec lesquels les groupes et les intervenantes doivent composer dans un contexte social et d’intervention qui se complexifie.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; femmes* racisées; histoire et politique; intersectionnalité; intervention féministe; maisons d'hébergement; militance; organisations féministes; périodes historiques; québec; recherche en milieux de pratique; ressource en ligne; régions géographiques; thématiques; travail

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis